THE INFLUENCE OF THE BIG FIVE PERSONALITY ON THE PSYCHOLOGICAL WELL-BEING OF CHILDREN IN AGAINST THE LAW - Umbas, Felisia Divina Jessy; Andhini, Luh Putu Ratih; Utami, Ni Made Sintya Noviana (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2024)
This study aims to determine the influence of big five personalities on psychological well-being in Law-Facing Children at LPKA. This study uses the psychological well-being scale and the big five inventory scale. The subjects in this study amounted to 35 ABH, the method used is quantitative with probability sampling techniques with a simple random sampling design. The hypothesis test used is a simple linear regression test. The results showed that there is an influence of the big five personalities on psychological well-being. This research is expected to be able to help the subject, the environment and the LPKA to understand and strive for the subject’s psychological well-being. Keywords: psychological well-being, big five personality, anak berhadapan hukum (ABH), lembaga pembinaan khusus anak (LPKA)